Arginine Metabolism in Supragingival Oral Biofilms as a Potential Predictor of Caries Risk. (July 2019) - Nascimento, M.M.; Alvarez, A.J.; Huang, X.; Hanway, S.; Perry, S.; Luce, A.; Richards, V.P.; Burne, R.A.
Introduction: Ammonia production via the arginine deiminase system (ADS) of oral bacteria can function to reduce the cariogenicity of oral biofilms by neutralizing glycolytic acids that cause tooth demineralization. Objectives: This cohort study investigated the relationship between ADS activity and bacterial profile changes of supragingival biofilms with caries experience among children over time. Methods: A total of 79 children aged 2 to 7 y at baseline were assessed every 6 mo for a period of 18 mo. Children were grouped as caries free (CF), caries active with enamel lesions (CAE), or caries active with dentin lesions (CA). Supragingival plaque samples were collected from caries-free surfaces (PF) and from enamel (PE) and dentin (PD) lesions. Plaque ADS activity was measured by monitoring citrulline production from arginine and compared with ribosomal 16S rRNA–derived taxonomic profiles for the same samples. Results: At baseline, 37% of the children were CF, 34% CAE, and 29% CA. At 18 mo, 26% were CF, 41% CAE, 23% CA, and 10% were caries experienced (new restorations but no caries activity). Throughout the study period, ADS activity was significantly higher in the CF group than the CA group (P < 0.0001), and ADS activity in the PF samples was significantly higher than in the PE and PD samples (P < 0.0001). Distance-based redundancy analysis showed that the bacterial communities could be differentiated when plaque samples are grouped into levels of high and low ADS activity. Conclusions: There is a positive correlation between caries activity and low arginolytic capacity of the supragingival oral biofilms of children and tooth surfaces over time. Measurements of arginine metabolism via ADS may be useful to differentiate the caries risk of individuals and tooth surfaces. Knowledge Transfer Statement: Findings from this study support the development of new strategies for caries risk assessment and prevention based on modulation of the virulence of the oral microbiome through arginine metabolism in supragingival biofilms.